BEST PRACTICE PELAYANAN ADMINISTRASI KEPENDUDUKAN KABUPATEN KUDUS - Listyaningsih Dewi Pamungkas; Rukhana Fitriati (Magister Administrasi Publik, FISIP, 2019)
This study aims to analyze the concept of best practice at the Population Administration and Civil Registration office of Kudus Regency. The study is implemented by applying the qualitative descriptive research methods. In terms of theoretical framework, the article refers to best practice theory. Best practice theory suggests criteria to examine policy innovation, namely impact, partnerships, sustainability, leadership, and innovations in local contexts that can be transferred (transferability). The results of this study indicate that the Population Administration and Civil Registry especially in the Civil Registry Population Service is categorized as good and feasible as a